STUDI IN SILICO INTERAKSI KOBALT DAN MERKURI TERHADAP PROTEIN PADA KEJADIAN DIABETES MELITUS - Aranda, Viren Lolita; Suhartono, Eko; Fujiati, Fujiati; Mashuri, Mashuri; Setiawan, Bambang (Universitas Lambung Mangkurat, 2023)
The coal mining industry in South Kalimantan can cause heavy metal waste pollution in the aquatic environment if not managed wisely. Cobalt and mercury are heavy metals that can cause disruption of glucose homeostasis which can lead to diabetes mellitus. The toxicity of cobalt and mercury occurs as a result of interactions with proteins associated with diabetes mellitus, namely insulin receptors, PPARγ, protein kinase b and c-reactive protein. This study aims to determine the interaction of heavy metals cobalt and mercury on insulin receptors, PPARγ, protein kinase b and c-reactive protein with PDB ID: 2HR7, 1PRG, 3E87, 1GNH taken from the Protein Data Bank and using the molecular docking website MIB2: Metal Ion-Binding site prediction and modeling server. Docking results were visualized using the Chimera ver 1.16 application. Based on the docking results, it was found that the interaction between cobalt and mercury with insulin receptors, PPARγ, protein kinase b and c-reactive protein. Cobalt has the highest potential to bind to insulin receptors. While mercury has the highest potential to bind to protein kinase b. Mercury binds more strongly to insulin receptors, PPARγ, protein kinase b and c-reactive protein than cobalt. This interaction causes changes in protein conformation that have the potential to inactivate protein function.